Nilai Kearifan Lokal Industri Gerabah Bumi Jaya Dalam Pembelajaran Sejarah Kelas X di SMA Negeri 1 Ciruas - Indah Pratiwi; Agus Rustamana; Ana Nurhasanah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to describe the value of local wisdom of the Bumi Jaya pottery industry in learning history for class X at SMA Negeri 1 Ciruas including the historical development of pottery craft that developed in Bumi Jaya village, the characteristics of the pottery craft that are characteristic of Bumi Jaya pottery production, as well as the efforts made so that the values ​​of local wisdom in the art of pottery in the village of Bumi Jaya in learning history for class X students of SMA Negeri 1 Ciruas. The method in this study uses a qualitative approach with a case study method. Data collection techniques were carried out through interviews, documentation studies, and observations with analytical methods, namely data collection, data reduction, data presentation, and verification. Based on the results of the study, it can be concluded that historical learning correlates local historical sources, namely the Earth Jaya pottery industry, as a source of learning history for students of SMA Negeri 1 Ciruas. The earthenware industry of Bumi Jaya is a form of culture that grows in the community providing use values, economic values, and aesthetic values ​​which are part of the value of local wisdom. Keywords: Value of Local Wisdom, Bumi Jaya Pottery, History Learning.